HOXA1 3′UTR Methylation Is a Potential Prognostic Biomarker in Oral Squamous cell Carcinoma - Sorroche, Bruna Pereira (2024)
Background: HOXA1 is a prognostic marker and a potential predictive biomarker for radioresistance in head and neck tumors. Its overexpression has been associated with promoter methylation and a worse prognosis in oral squamous cell carcinoma (OSCC) patients. However, opposite outcomes are also described. The effect of the methylation of this gene on different gene regions, other than the promoter, remains uncertain. We investigated the methylation profile at different genomic regions of HOXA1 in OSCC and correlated differentially methylated CpG sites with clinicopathological data. Methods: The HOXA1 DNA methylation status was evaluated by analyzing data from The Cancer Genome Atlas and three Gene Expression Omnibus datasets. Significant differentially methylated CpG sites were considered with a |∆β| ≥ 0.10 and a Bonferroni-corrected p-value < 0.01. Differentially methylated CpGs were validated by pyrosequencing using two independent cohorts of 15 and 47 OSCC patients, respectively. Results: Compared to normal tissues, we found significantly higher DNA methylation levels in the 3′UTR region of HOXA1 in OSCC. Higher methylation levels in tumor samples were positively correlated with smoking habits and patients’ overall survival. Conclusions: Our findings suggest that HOXA1 gene body methylation is a promising prognostic biomarker for OSCC with potential clinical applications in patient monitoring.